A great miracle = Ang dakilang himala - Ordinario, Mary Ann (ABC Educational Development Center, 2003)
"In this story, we will feel the woman's faith upon God as she tried to do something valuable, lasting and meaningful by sewing three fabrics. The first fabric wrapped a most precious gift on Earth. The second fabric was worn by the greatest master, and the third fabric showed the image of the son of God. Till the day the woman was afflicted with illness, she never knew that the cloth she has sewn and touched were her great offerings to God."--Back cover.